(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The rapid digitalization of higher education has increased the need for systematic planning and effective management of e-learning initiatives. This study examines the process of planning and managing an e-learning project for English language teaching in a private higher education institution. The research focuses on project stages, resource management, implementation challenges, and practical outcomes. The findings show that applying structured project management frameworks improves course organization, student engagement, and the overall effectiveness of digital learning.